The Factors Affecting People’s Decision-Making in the Election of the Subdistrict Administrative Organization President in Waeng Noi District, Khon Kaen Province - Sinso, Paradee; Sawattha, Suthiphong; Promkun, Suraphon (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were: 1) to study the level of people’s decision-making 2) to study the factors affecting people’s decision-making and 3) to study the suggestions of people’s decision-making in the election of the Subdistrict Administrative Organization President in Waeng Noi District, Khon Kaen Province by applying the principles of Four Brahmavihra. The sample group included 394 people in Waeng Noi District, Khon Kaen Province, and 12 key informants. The tools used were a questionnaire and an interview form. Data were analyzed using social science software packages and contextual content analysis. The research results were as follows: 1) The overall level of people’s decision-making in the election of the Subdistrict Administrative Organization President in Waeng Noi District was statistically rated at a high level ( = 3.89). From an aspect perspective, the aspect with the highest mean was the electoral decision ( = 4.18), followed by the characteristics of applicants ( = 4.00), the candidate’s campaign ( = 4.00), the policy of the applicants ( = 3.97), the Four Brahmavihra and personal relationship with the applicant ( = 3.23). 2) The factors affecting people’s decision-making in the election of the Subdistrict Administrative Organization President were that the candidate’s characteristics had a positive influence on people’s decision-making in the election of the Subdistrict Administrative Organization President. That is, when the candidate’s attributes increase by one unit, the decision of the people in the election of the Subdistrict Administrative Organization President will change by 0.10 units. The Four Brahmavihra Principles had a positive influence on people’s decision-making in the election of the Subdistrict Administrative Organization President. That is, an increase of 1 unit of the Four Brahmavihra principles will change the decision of the people in the election of the president of the Subdistrict Administrative Organization by 0.16 units. 3) The suggestions of people’s decision-making in the election of the Subdistrict Administrative Organization President in Waeng Noi District, Khon Kaen Province were that the Election Commission of Thailand should encourage the public to be informed about the qualifications of candidates before making an election decision. It should encourage people to make electoral decisions by applying the Four Brahmavihra principles to make decisions. It should encourage the publicity of the applicant’s policies to the general public and campaign to promote the characteristics of candidates and works in various fields of applicants who have made contributions to people and communities so that people have as much information as possible before making an election decision.